Spermidine-Regulated Biosynthesis of Heat-Stable Antifungal Factor (HSAF) in Lysobacter enzymogenes OH11 - Chen, Yuan; Yu, Lingjun; Liu, Fengquan; Du, Liangcheng (Frontiers in Microbiology, 2018)
Heat-Stable Antifungal Factor (HSAF) and its analogs are antifungal natural products produced by the biocontrol agent Lysobacter enzymogenes. The production of HSAF is greatly influenced by environmental stimuli and nutrients, but the underlying molecular mechanism is mostly unclear. Here, we found that HSAF production in L. enzymogenes OH11 is strictly controlled by spermidine, which is the most prevalent triamine in bacteria. When added into OH11 cultures, spermidine regulated the production of HSAF and analogs in a concentration-dependent manner. To verify the role of spermidine, we deleted LeSDC and LeADC genes, encoding S-adenosylmethionine decarboxylase and arginine decarboxylase respectively, that are the key enzymes for spermidine biosynthesis. Both deletion mutants produced barely detectable spermidine and HSAF including its analogs, whereas the antifungals production was restored by exogenous spermidine. The results showed that the OH11 cells must maintain a proper spermidine homeostasis for the antifungals production. Indeed, the expression level of the key HSAF biosynthetic genes was significantly impaired in LeSDC and LeADC mutants, and exogenous spermidine restored the gene expression level in the mutants. Ornithine is a key substrate for HSAF biosynthesis, and OH11 genome contains arg1 and arg2 genes, encoding arginases that convert arginine to ornithine. While the expression of arg1 and arg2 was affected slightly upon mutation of LeSDC and LeADC, exogenous spermidine significantly increased the arginase gene expression in LeSDC and LeADC mutants. Together, the data revealed a previously unrecognized mechanism, in which spermidine controls antibiotic production through controlling both the biosynthetic genes and the substrate-production genes.